The Production of Safety School Space from Climate Disasters in Doi Mae Salong Forest, Upland Northern Thailand - Dania, Maya; Inpin, Wanwalee; Juwitasari, Reni; Miyake, Yuki; Takeuchi, Yukiko; Maki, Takayoshi (Forestry Faculty, Universitas Hasanuddin, 2022)
This research is conducted in Santikhiri, a hilltop village on the highest peak in the Doi Mae Salong forest, where climate change increases the intensity and frequency of natural disasters that immensely affect the local children in the mountainous area in Chiang Rai province, northern Thailand. There is only one secondary-level school in this forest landscape educating around 900 schoolchildren from various minority hill-tribe ethnic groups. This paper examines everyday life experiences recentering the village school's role as the producer of safe space for the forest children from climate disasters. School safety is a global framework for recognizing the importance of child-centered efforts in building disaster resilience for the education sector. Parameters and variables used to measure the disaster resilience of schools are adapted from the Climate Resilience Model and School Safety Model by Tong et al. (2012), covering three dimensions: 1) institutional issues, 2) physical conditions, and 3) external relationships. Lefebvre's Spatial Triad Framework is applied to dialectically interconnect dimensions to produce a safe space at the village school to protect the students from climate disaster threats. A mix-method method is applied with several techniques to collect data, including participant observation, semi-structured interviews, and content analysis. Furthermore, a scale Likert survey examined statements on school safety from educational practitioners in the rural forest area. The research argues that the production of safe space at the school is intertwined with budget allocation for disaster preparedness and response (institutional issue as l'espace concu), environmental protection campaign to create a hygienic school environment (physical conditions as l'espace percu), and support from the local community (external relations as l'espace vecu). However, the school is also two contradicting spaces of conceived and lived. Through the critical examination of the production of safe space, the school is a planned space of hierarchical power relations in institutional issues focusing on impacts from rapid-onset disasters. Concurrently, the forest children are still marginalized from external relationships and natural conditions' slow-onset climate change impacts.